You'll solve this equation involving combinations using
the factorial formula for combinations of n elements taken k at a
time:
C(n,k) = n!/k!(n -
k)!
Let's evaluate C(n+1 , 3) = (n+1)!/3!(n+1-3)! =
(n+1)!/3!(n - 2)!
Let's evaluate C(n , 2) =
n!/2!(n-2)!
Now, we'll equate the equivalent
expressions:
(n+1)!/3!(n - 2)! =
n!/2!(n-2)!
We'll simplify both sides by
(n-2)!
(n+1)!/3! = n!/2!
We
can write (n+1)! = n!*(n+1)
We can write 3! =
2!*3
n!*(n+1)/2!*3 =
n!/2!
We'll simplify both sides by
n!/2!:
(n+1)/3 = 1
We'll cross
multiply:
n + 1 = 3
n = 3 -
1
n = 2
Since
the value of "n" has to be a natural number, therefore a positive integer, we'll accept
n=2 as solution of the given equation.
No comments:
Post a Comment